Why Play and Sing? The Role of Folk Games and Folk Songs in Everyday Life - Lázár, Katalin (Traditiones, 2005)
Playing helps us in learning and developing more kinds of skills, further in developing our emotional world, not only in traditional society but in any time and any place. Singing strengthens collective consciousness and identity. Besides, playing and singing as basic forms of entertainment assure enjoying ourselves to us. We have to learn and do them for the sake of living a perfect life: to be able to express our joy and to amuse ourselves. *** Igranje pomaga pri učenju in razvijanju številnih sposobnosti, pa tudi pri razvoju čustvenega sveta, ne le v tradicionalni družbi, ampak v katerem koli prostoru in času. Petje krepi kolektivno zavest in identiteto. Poleg tega igranje in petje kot osnovni obliki zabave zagotavljata, da uživamo tudi sami s seboj. Zato se ju moramo učiti in s petjem in igranjem izražati svoje veselje in se zabavati. playing help us in learning and developing more types of skills, further in developing our Emotional world, not only in traditional society but in any time and any place. Singing strengthens collective consciousness and identity. Besides, playing and singing as basic forms of entertainment ASSURE enjoying Ourselves to us. We have to learn and do them for the sake of living a perfect life: to be able to express our Joy and to amuse Ourselves. *** Gaming helps to learn and develop many skills, as well as to develop an emotional world, not only in traditional society, but in any space and time. Singing strengthens collective consciousness and identity. In addition, playing and singing, as a basic form of entertainment, ensures that we enjoy ourselves. That’s why we need to learn and to express their pleasure and fun by singing and playing.